Private Affairs : A Novel - Michael, Judith (London Sphere Books Ltd., 1986)
First published in 1986. It tells the story of an affluent couple who risk everything they own to pursue their dream of buying a newspaper.
English Fiction.
Keywords: Marriage -- United States -- Adultery